Callus induction anther culture of honeydew (cucumis melo) using Naa - Nurul Hasanah Ibrahim (2022)
Anther culture is a quick and easy way to make haploids from the microspores found in the intact anther. The effect of cultivated anther is more prevalent at various maturation phases in young anther, particularly in the field-growed than in average the grown plants. Callus is created to produce embryos where haploid plants are made and transferred to another media. Callus induction is more common. The significance of this study is to observe the development and growth of callus from anther culture of Cucumis melo treated with 1 naphthaleneacetic acid (NAA). The objective of the project is to find the suitable amount of NAA to be used in media for inducing callus develop post-induction.